Mechanistic aspects of the photodynamic inactivation of Candida albicans induced by cationic porphyrin derivatives - Quiroga, Ezequiel Dario (2012)
Photodynamic inactivation of Candida albicans produced by 5-(4-trifluorophenyl)-10,15,20-tris(4-N,N,N-trimethylammoniumphenyl)porphyrin (TFAP3+), 5,10,15,20-tetrakis(4-N,N,N-trimethylammoniumphenyl) porphyrin (TMAP4+) and 5,10,15,20-tetrakis(4-N-methylpyridyl) porphyrin (TMPyP4+) was investigated to obtain insight about the mechanism of cellular damage. In solution, absorption spectroscopic studies showed that these cationic porphyrins interact strongly with calf thymus DNA. The electrophoretic analysis indicated that photocleavage of DNA induced by TFAP3+ took place after long irradiation periods (>5 h). In contrast, TMAP4+ produced a marked reduction in DNA band after 1 h irradiation. In C. albicans, these cationic porphyrins produced a ∼3.5 log decrease in survival when the cell suspensions (107 cells/mL) were incubated with 5 μM photosensitizer and irradiated for 30 min with visible light (fluence 162 J/cm2). After this treatment, modifications of genomic DNA isolated from C. albicans cells were not found by electrophoresis. Furthermore, transmission electron microscopy showed structural changes with appearance of low density areas into the cells and irregularities in cell barriers. However, the photodamage to the cell envelope was insufficient to cause the release of intracellular biopolymers. Therefore, modifications in the cytoplasmic biomolecules and alteration in the cell barriers could be mainly involved in C. albicans photoinactivation.